Tindak Pidana Kejahatan Pencucian Uang (Money Laundering) Serta Perlindungan Hukum Bagi Korban - Naufal Wahyu Nabiha; Umi Enggarsasi (Pusat Riset dan Inovasi Nasional, 2024)
Money Laundering is an attempt to hide or disguise the origin of money or assets resulting from a criminal act through various financial transactions so that the money or assets appear as if they came from legal activities. The criminal act of money laundering is increasingly complex, and uses increasingly varied methods, one of the crimes originating from money laundering is fraud. The problems studied are how the law protects victims of fraud, what is the mechanism for confiscating and returning assets resulting from criminal acts originating from the assets of fraud victims, as well as an analysis of the basic considerations of judges in the Supreme Court decision no. 3096 K/Pid.Sus/2018. The defendant, who was proven to have not only committed the crime of